Pelestarian Kampung Pecinan di Desa Karangturi, Kecamatan Lasem - Brillian Syafiria; Nurini Nurini (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
Karangturi Village, located in center of Lasem District is in a strategic location close to the pantura street and a large mosque in Lasem, the Jami 'Mosque has historical potential associated with traditional Lasem batik making, traditional cake making, and ancient building distribution. This is an advantage as well as a challenge for the government, because its location is at the center of activity prone to social and physical changes of the ancient buildings. Therefore, Kampung Pecinan in Karangturi Village needs to be preserved to be able to maintain the existence of the area. This study aims to identify efforts to conserve Kampung Pecinan in Karangturi Village. The methods used in this study is a quantitative method of scoring analysis techniques performed by experts. Scoring analysis conducted in the study aims to strengthen the description of the results of the analysis conducted to facilitate the identification of Kampung Pecinan buildings in Village Karangturi. The results of the assessment by legal experts on the feasibility of historic area and buildings, as well as community activities where three things deserve to be preserved with preservation forms for the region, 14 ancient buildings with preservation, and six ancient buildings with a form of preservation of restoration / rehabilitation, and preservation for community activities.